Morphological and biochemical characterization of bacterial species of Bacillus, Lysinibacillus and Brevibacillus - Teodoro Rocha, Gabriela; Coelho Linhares Montalvão, Sandro; Martins Queiroz, Paulo Roberto; Rodrigues Berçot, Marcelo; Meneses Mendes Gomes, Ana Cristina; Gomes Monnerat, Rose (Revista Ceres, 2023)
The objective of this work was to characterize reference bacteria strains, belonging to the genus Bacillus and species of correlated genera, by simplified morphological and biochemical methods. The morphological characterization is based on the aspects of the colonies, as well as cytomorphology of the species, by optical and scanning microscopy. For biochemical characterization, the sensitivity test to antimicrobials by disk-diffusion is performed. Moreover, the strains were characterized by extracting intracellular proteins. Characteristics such as shape, color, and consistency of the colonies, in addition to the type of spore and production of protein crystals were determinants for the morphological characterization of these species. The antibiogram revealed high resistance to β-lactam group antibiotics, in species of Bacillus cereus s.l group. In Bacillus subtilis s.l. group there was high susceptibility to antibiograms, mainly for species of B. subtilis. The protein profile provided specific protein patterns for some species, mainly bands of 130 e 65 kDa for B. thuringiensis, 140 e 130 kDa for Lysinibacillus sphaericus, and 115 kDa for Brevibacillus laterosporus. Our results showed that the morphological and biochemical characterizations, provided a simple identification, with easy interpretation, and low cost.